Time from ECG Diagnosis to sheath insertion is a strong predictor for mortality in patients with ST elevation myocardial infarction admitted for primary percutaneous coronary intervention. (25th November 2020) - Larsen, A.I; Loland, K; Hovland, S; Bleie, O; Trovik, T; Hegbom, K; Larsen, T; Fossum, E; Eek, C; Moer, R; Juliebo, V; Uchto, M; et al.
Abstract: Introduction: If reperfusion can be performed within 120 minutes, pPCI is the ESC guideline recommended treatment in patients with ST-elevation myocardial infarction (STEMI). Aims: Historically, prognosis is dependent on time from diagnosis to reperfusion in patients with STEMI. We sought to investigate this in a contemporary patient population by assessing mortality as function of time from ECG diagnosis to sheath insertion in the Norwegian registry for invasive cardiology (NORIC). Methods: NORIC, which is a part of the Norwegian Cardiovascular Disease Registry, is a national, mandatory and non-consensual person-identifiable health registry. Data from NORIC were linked with the National Population Register. Data were registered from 1st of January 2013 to 31st of June 2019. Results: During this period complete data were available for n=5754 patients with 526 events. ECG diagnosis to sheath insertion was a predictor of mortality with the 4th (>106 min) vs 1st quartile (<54 min) with a HR of 1.74 (95% CI 1.36–2.22), p-value <0.00001. The HR increased by 1.20 (95% CI 1.11–1.30) per quartile (p-value for trend <0.00001). Nationally 62% percent of the patients received pPCI within the ESC recommended 90 minutes from ECG-diagnosis with large geographical variation (range 38–89%). Nationally 80% received pPCI within 115 minutes (range 75–202 minutes). Conclusion: In a contemporary STEMI population, time from ECG diagnosis to sheath insertion is a strong predictor for mortality in patients admitted for pPCI for STEMI. However, the data also demonstrate large variations between different geographical health regions in Norway that should be addressed. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Haukeland University Hospital